2005
DOI: 10.1007/s00122-005-2008-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of gibberellin-responsive dwarfing genes in bread wheat

Abstract: Opportunities exist for replacing reduced height (Rht) genes Rht-B1b and Rht-D1b with alternative dwarfing genes for bread wheat improvement. In this study, the chromosomal locations of several height-reducing genes were determined by screening populations of recombinant inbred lines or doubled haploid lines varying for plant height with microsatellite markers. Linked markers were found for Rht5 (on chromosome 3BS), Rht12 (5AL) and Rht13 (7BS), which accounted for most of the phenotypic variance in height in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 14 publications
4
164
2
3
Order By: Relevance
“…Worland and Law (1985) reported that the distribution of GAinsensitive dwarfing genes (Rht-B1b and Rht-D1b) is restricted to areas where heat and drought stress condition prevails during grain filling. Ellis et al (2005) have suggested that both Rht-1 dwarfing alleles (Rht-B1b and Rht-D1b) also negatively affect the growth of young plants, but that this effect is not mirrored by Rht-8. Therefore, Rht-8 might be more suitable in reducing final plant height, without compromising early plant growth (Ellis et al, 2005).…”
Section: Biplot Analysismentioning
confidence: 99%
“…Worland and Law (1985) reported that the distribution of GAinsensitive dwarfing genes (Rht-B1b and Rht-D1b) is restricted to areas where heat and drought stress condition prevails during grain filling. Ellis et al (2005) have suggested that both Rht-1 dwarfing alleles (Rht-B1b and Rht-D1b) also negatively affect the growth of young plants, but that this effect is not mirrored by Rht-8. Therefore, Rht-8 might be more suitable in reducing final plant height, without compromising early plant growth (Ellis et al, 2005).…”
Section: Biplot Analysismentioning
confidence: 99%
“…Molecular markers have been used extensively to incorporate qualitative and quantitative traits into new cultivars (Ellis et al, 2005). Rht genes have strong foundation in wheat; semi-dwarf alleles were important component of the green revolution, which helped avoid major worldwide food shortages (Wilhelm et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes have been *Corresponding authors (email: penghuiru@cau.edu.cn; qxsun@cau.edu.cn) exploited to breed many semidwarf cultivars with high yield potential. Recently, along with the advent of molecular quantitative genetics, about 50 quantitative trait loci (QTLs) for wheat plant height have been identified using the constructed molecular genetic linkage maps [3][4][5][6][7][8][9][10][11][12][13][14][15]. However, QTL mapping of plant height in wheat was only focused on the performance of this trait at the maturing stage.…”
mentioning
confidence: 99%